2014
DOI: 10.1007/s13187-014-0718-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of a Colonoscopy Screening Navigator Program Designed for Hispanic Men

Abstract: Although Hispanic men are at higher risk of developing colon cancer compared to non-Hispanic white men, colonoscopy screening among Hispanic men is much lower than among non-Hispanic white men. University Health System (UHS) in San Antonio, Texas, instituted a Colorectal Cancer Male Navigation (CCMN) Program in 2011 specifically designed for Hispanic men. The CCMN Program contacted 461 Hispanic men 50 years of age and older to participate over a 2-year period. Of these age-eligible men, 370 were screened for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(81 citation statements)
references
References 23 publications
0
81
0
Order By: Relevance
“…Three years into the first 6-year cycle of the program, a hypothetical 5% and 10% increase in compliance would have resulted in a screening promotion cost per person of under $100 and $50 respectively. Studies have shown that evidence-based promotion activities can increase screening utilization (Ladabaum, Mannalithara, Jandorf, & Itzkowitz, 2015; Pinkowish, 2009; Sabatino et al, 2012; Wilson, Villarreal, Stimpson, & Pagan, 2015) but the design of the CRCCP promotion interventions did not allow for program impacts to be assessed independent of overall state population level impacts. The findings from this study can therefore assist policy makers to assess the potential cost and benefit of the program and provide effectiveness thresholds to guide future program funding decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Three years into the first 6-year cycle of the program, a hypothetical 5% and 10% increase in compliance would have resulted in a screening promotion cost per person of under $100 and $50 respectively. Studies have shown that evidence-based promotion activities can increase screening utilization (Ladabaum, Mannalithara, Jandorf, & Itzkowitz, 2015; Pinkowish, 2009; Sabatino et al, 2012; Wilson, Villarreal, Stimpson, & Pagan, 2015) but the design of the CRCCP promotion interventions did not allow for program impacts to be assessed independent of overall state population level impacts. The findings from this study can therefore assist policy makers to assess the potential cost and benefit of the program and provide effectiveness thresholds to guide future program funding decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This is significant given that Hispanics already lag behind other ethnic groups in completing CRC screening. 34,35 As there is no data to suggest that Hispanic patients are more tolerant of colonoscopy compared with other ethnicities, our findings indicate that lack of adequate sedation during colonoscopy in the Hispanic population may potentiate underutilization of colonoscopy among this group of patients. Other investigators have shown that culturally tailored approaches to colonoscopy referral can increase colonoscopy completion rates among minority ethnicities; cultural sensitivity immediately prior and during colonoscopy might further insure adequate sedation during colonoscopy.…”
Section: Discussionmentioning
confidence: 72%
“…Colonoscopy navigator programs can range in cost from $50 to $500 per patient. 12, 13 Screening colonoscopy is also widely considered cost-effective as compared to other screening activities. 14 Since the intervention used email communication and existing call center operations, it would require minimal additional staff resources.…”
mentioning
confidence: 99%